Política de indexação e linguagem documentária em universidades federais brasileiras - Silva, Lidya Nágylla de Almeida (2024)
In the scope of Information Science, especially in the area of Information and Knowledge Representation, it is of the utmost importance that scientific production is properly represented and organized. After identifying that the Institutional Repository of the Federal University of Ceará does not have its own Indexing Language or Indexing Policy, the question arose as to whether this was an isolated phenomenon or whether it was recurrent among the Federal Universities of Brazil, especially among those with undergraduate and postgraduate degrees in Library Science and Information Science. The general objective of this research is to investigate the relationship between the existence of Library Science and Master's and Doctoral programmes in Information Science and the existence, or not, of Indexing Policies and Indexing Languages at Federal Universities in Brazil. In order to achieve the above-mentioned objective, the following specific objectives were outlined: 1) to find out whether the Federal Universities have Indexing Policies and Indexing Languages that include the Library System and the Institutional Repository; 2) to examine whether the Federal Universities have undergraduate degrees in Library Science and postgraduate degrees in Information Science. According to Cintra (2002), the aim is to deepen the level of knowledge in the aforementioned area, emphasizing the scientific knowledge produced by Universities. As a result of the data collected, it was identified that only 25 Federal Universities (36% the sample), of a total 69, have a degree in Library Science and that only 7 (10%) of these have an Indexing Policy. Despite the fact that 2 Federal Universities (3% of the sample) have Indexing Policies even without a degree course in Library Science, it was also observed that the existence of Federal Universities is concentrated in the Federal Universities that have the Library Science course, but still in smaller numbers. Thus, it can be concluded that even if there is a relationship between the existence of courses and the creation of an Indexing Policy or Indexing Language for the Federal Universities, this is not a preponderant and indispensable factor. It is recommended a federal pact for the creation and development of research in the area of Knowledge Representation. It should be emphasised that the implementation of an Indexing Policy and an Indexing Language is of the utmost importance in order to optimise the representation and retrieval of information deposited in Institutional Repositories.